Conservation of the Black-collared Swallow, Pygochelidon melanoleuca (Wied, 1820) (Aves: Hirundinidae) in Brazil: potential negative impacts of hydropower plants - Silva, Gabriele Andreia da; Frederico, Renata Guimarães; Almeida, Sara Miranda; Salvador, Gilberto Nepomuceno; Malacco, Gustavo Bernardino; Melo, Celine de (Biota Neotropica, 2022)
Abstract: We analyzed the overlap of the range of Pygochelidon melanoleuca in Brazil with active and planned hydropower plants in the country (current and future scenarios). We used the Random Forest, Maxent and Support Vector Machine algorithms to model the potential range of the species, which we then overlapped with the locations of active and planned hydropower plants in order to calculate how much the potential area of this species is and will be affected by them. Approximately 35% of active hydropower plants currently overlap with the potential distribution area of P. melanoleuca, and 44% of planned hydropower plants also coincide with this area. If the implementation of the planned hydropower plants occurs, the suitable habitat necessary for nesting and foraging of P. melanoleuca will be severely compromised.